One minute preceptor as an effective teaching and learning method for pediatric internship: An interventional study - Iyer, Chandrakala R; Nanditha, G; Raman, Janaki (Indian Journal of Child Health, 2022)
Background: Compulsory Rotating Residential Internship (CRRI) is an important learning period for medical graduates to become competent registered medical practitioners. Exclusive teaching programs for interns are scarce. During short pediatric CRRI postings, it is difficult to disseminate the necessary knowledge and skills to manage the common pediatric problems seen in the community by traditional teaching methods. We explored innovative teaching techniques to train the interns in a short time to acquire such basic skills. One minute preceptor (OMP) is a five micro skills clinical teaching, tailored to the learner’s needs by motivating them to learn. Objective: To implement OMP in our busy pediatric outpatient department (OPD) to train the interns andto know if it is an effective teaching technique. Methods: The study group included 15 interns who were posted to pediatric OPD on rotation for a month and never had earlier OMP teaching module. Their learning experience with traditional teaching method was gathered by a validated pre-project questionnaire graded on Likert scale. After 3 OMP sessions with a trained faculty, their learning experience was again collected by a post-project questionnaire. The data were compared and analyzed statistically using stata14 version software. p